2016
DOI: 10.1038/srep35446
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a silver particle-integrated silicone polymer-covered metal stent against sludge and biofilm formation and stent-induced tissue inflammation

Abstract: To reduce tissue or tumor ingrowth, covered self-expandable metal stents (SEMSs) have been developed. The effectiveness of covered SEMSs may be attenuated by sludge or stone formation or by stent clogging due to the formation of biofilm on the covering membrane. In this study, we tested the hypothesis that a silicone membrane containing silver particles (Ag-P) would prevent sludge and biofilm formation on the covered SEMS. In vitro, the Ag-P-integrated silicone polymer-covered membrane exhibited sustained anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
0
19
0
1
Order By: Relevance
“…Research trends show that physicians are mainly focused on the mechanical aspects of SEMS to increase patency, and the structure and composition of these stents are constantly evolving [31][32][33][34]. Despite this, the need for improved stent patency has not been met because of the lack of research on chemical prophylaxis for stent patency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research trends show that physicians are mainly focused on the mechanical aspects of SEMS to increase patency, and the structure and composition of these stents are constantly evolving [31][32][33][34]. Despite this, the need for improved stent patency has not been met because of the lack of research on chemical prophylaxis for stent patency.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that aspirin leads to cell apoptosis by inhibiting Bcl-2 expression and downregulating COX-2 expression, which is known to convert arachidonic acid to prostaglandins, and it may reduce tumorcell invasion through the downregulation of MMP-2 expression [41,42]. Some studies have also provided evidence that aspirin promotes deoxyribonucleic acid (DNA) self-healing by the upregulation of hMLH1, hMSH2, hMSH6, hPMS2 [43], and XRCC expression [44], slowing down gene-mutation accumulation, and protecting normal cell DNA [32,45]. Recent studies have suggested several new aspirin pathways, such as inhibiting the synthesis of prostaglandin E2 (PGE2) [46], controlling the number of circulating platelets and their activity levels to evade several innate anti-tumor effects [47][48][49][50], increasing chemo-agent toxicity, and downregulating cellular drug resistance [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…[30] Research trends show that physicians are mainly focused on the mechanical aspects of SEMS to increase patency, and the structure and composition of these stents are constantly evolving. [31][32][33][34] Despite this, the need for improved stent patency has not been met because of the lack of research on chemical prophylaxis for stent patency. Based on the study of Jang et al, [11] we will investigate whether aspirin use after index ERBD with SEMS for malignant distal CBD obstruction is effective and safe.…”
Section: Discussionmentioning
confidence: 99%
“…[27] Research trends show that physicians are mainly focused on the mechanical aspects of SEMS to increase patency, and the structure and composition of these stents are constantly evolving. [28][29][30][31] Despite this, the need for improved stent patency has not been met because of the lack of research on chemical prophylaxis for stent patency. Based on the study of Jang et al, [11] we will investigate whether aspirin use after index ERBD with SEMS for malignant distal CBD obstruction is effective and safe.…”
Section: Discussionmentioning
confidence: 99%
“…[38,39] Some studies have also provided evidence that aspirin promotes DNA self-healing by the upregulation of hMLH1, hMSH2, hMSH6, hPMS2, [40] and XRCC expression, [41] slowing down gene mutation accumulation, and protecting normal cell DNA. [29,42] Recent studies have suggested several new aspirin pathways, such as inhibiting the synthesis of PGE2, [43] controlling the number of circulating platelets and their activity levels to evade several innate anti-tumor effects, [44][45][46][47] increasing chemo agent toxicity, and downregulating cellular drug resistance. [48,49] Since the results of these basic studies have mostly been conducted in vitro and have not been proven in humans, these outcomes cannot be presented as definitive mechanisms of aspirin.…”
Section: Discussionmentioning
confidence: 99%